The synthesis of regional navigation system support in Ukraine - Скорик E. T.; Волох, К. Ф. (Proceedings of National Aviation University (archive), 2000)
Considered is the problem of synthesis of national (autonomous) satellite navigation system in Ukraine. As an alternative to medium orbital system GPS and ГЛОНАСС proposed is original model using geostationary communication satellites visible from the territory of Ukraine. It is proposed to use leased resources of communication satellites by retransmission of special navigation systems formed by ground stations. Considered are the interrogator active and non-interrogator passive navigation regimes. Carried out is a mathematic experiment on evaluation of accurate characteristics of three-dimensional passive determination of object position in coordinates of Ukrainian territory. The simulation results proved the possibility of using autonomous system of medium latitude with accuracies sufficient to solve a series of locality finding problems